A criatividade urbana como estratégia de competitividade - Simas, Sónia Cristina de Oliveira (2011)
A crescente migração urbana tem vindo a alertar para a emergência da criação de novos padrões de adaptabilidade e habitabilidade social e cultural, que possibilitem a concentração desta pluralidade e diversidade humana emergente. Onde a qualidade de vida, se torna o objectivo fulcral e onde surge a necessidade de criar uma nova dinâmica urbana, baseada num conhecimento sustentável e numa criatividade permanente, que surja como resposta imediata às sucessivas mudanças. A criatividade é uma nova abordagem na economia e na política urbana. As cidades criativas, os clusters e indústrias criativas, surgem como esta resposta urgente e necessária, para o emergir da economia criativa, que é, por sua vez, o passaporte para todas as sociedades futuras. Pretende-se apresentar um leque de estratégias orientadoras, que permitam a implementação de um plano para as cidades criativas, valorizando o papel da cultura local, como fonte inspiradora e impulsionadora desta criatividade urbana. Estas estratégias assentam no delinear de modelos e políticas de governação, que tenham por base a participação e a colaboração entre os governantes e a população local, orientando as mentalidades à criatividade. A viabilidade urbana futura deverá ter em consideração a existência e a ligação de factores, como o capital criativo, a competitividade, a sustentabilidade, as indústrias criativas, a cultura e a qualidade de vida. ABSTRACT: Increasing urban migration has inspired a debate about the need for new approaches and standards for adapting urban areas to an emerging diversification of its residents. The reorientation of current models towards new modes of social and cultural adaptability may represent a solution to this problem. Demands for improved quality of urban life are high and growing hence the pressures for creating new urban dynamics based on sustainable consumption patterns to propel creativity forwards, thus contributing to the emergence of creative production in a climate of successive changes. Creativity is a new approach in urban economics and policy. Creative cities, clusters and creative industries are attractive because they are orientated towards the future. In a climate of uncertainty, creative cities are increasingly seen as alternatives to traditional models of culture-led urban development. It is suggested that overcoming the problems associated with urban development require the participation of all parties concerned. Partnerships between local government and other stakeholders pose a critical challenge to meet the opportunities for achieving solutions to existing urban problems. This study explores theoretical issues, models and public policies concerning problems associated with operating partnerships in the pursuit of urban development that may lead to an increase in the application of creativity. Various strategies are proposed for the planning of creative cities to add value to the rich cultural heritage and promote cultural innovation. The implementation of such development strategies creates new prospects that warrant attention to varied elements, including creative capital, competitiveness, sustainability, creative industries, cultural heritage and quality of life.